Detection and localization of early- and late-stage cancers using platelet RNA - In 't Veld, Sjors G J G; Arkani, Mohammad; Post, Edward; Antunes-Ferreira, Mafalda; D'Ambrosi, Silvia; Vessies, Daan C L; Vermunt, Lisa; Vancura, Adrienne; Muller, Mirte; Niemeijer, Anna-Larissa N; Tannous, Jihane; Meijer, Laura L; et al. (Cancer cell, 2022)
Cancer patients benefit from early tumor detection since treatment outcomes are more favorable for less advanced cancers. Platelets are involved in cancer progression and are considered a promising biosource for cancer detection, as they alter their RNA content upon local and systemic cues. We show that tumor-educated platelet (TEP) RNA-based blood tests enable the detection of 18 cancer types. With 99% specificity in asymptomatic controls, thromboSeq correctly detected the presence of cancer in two-thirds of 1,096 blood samples from stage I-IV cancer patients and in half of 352 stage I-III tumors. Symptomatic controls, including inflammatory and cardiovascular diseases, and benign tumors had increased false-positive test results with an average specificity of 78%. Moreover, thromboSeq determined the tumor site of origin in five different tumor types correctly in over 80% of the cancer patients. These results highlight the potential properties of TEP-derived RNA panels to supplement current approaches for blood-based cancer screening.